My not so perfect life a novel - Kinsella, Sophie (New York Dial Press, 2017)
"When Katie Brenner is fired from her dream job in advertising in London, she's desperate to get away from her mad boss Demeter, and her crush, Alex, who she thought shared her feelings of adoration but didn't. Seeking refuge, she goes home to her father's farm in Somerset to help make her stepmother's dream of turning their land into a glamping retreat come true. Applying her savvy marketing smarts, Katie masterminds a glamorous upscale resort. But when Demeter shows up unnannounced, with Alex not far behind, Katie is forced to rethink her revenge fantasies and her assumptions about family, love, and office politics and realize how much she may have misjudged everyone--and everything--around her"-- Provided by publisher.
Keywords: Man-woman relationships--Fiction.